Demon slayer = Kimetsu no yaiba. Volume 20, The path of opening a steadfast heart - Gotoge, Koyoharu, 1988- (Shonen Jump manga., 2021)
"In Taisho-era Japan, kindhearted Tanjiro Kamado makes a living selling charcoal. But his peaceful life is shattered when a demon slaughters his entire family. His little sister Nezuko is the only survivor, but she has been transformed into a demon herself! Tanjiro sets out on a dangerous journey to find a way to return his sister to normal and destroy the demon who ruined his life... After their initial confrontation with Kokushibo, the most powerful of Muzan's demons, Tokito is severely wounded and Genya has been cut in half--but is still alive! Can his regenerative power heal even this fatal wound? Then the Hashira Himejima and Sanemi square off against Kokushibo and unleash all the skill they have against him. Himejima is blind, but if he can see into the Transparent World, he might have a chance. Who will survive this whirlwind of flashing blades?"--Provided by publisher.